2010
DOI: 10.1080/01639370903535726
|View full text |Cite
|
Sign up to set email alerts
|

Program for Cooperative Cataloging: BIBCO Records: Analysis of Quality

Abstract: The Program for Cooperative Cataloging (PCC) is an international program that brings together

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…14 While this was a case study of a manual e-book cataloging project rather than a batchloading project, Preston noted that "concerns about bibliographic record accuracy, retrievability, and adherence to cataloging standards" 15 17 She found that the majority of corrections could be viewed as minor and did not affect catalog retrieval, including changes to punctuation, diacritics, and spaces. El-Sherbini also identified corrections that might affect access, including indicators, subfields and delimiters, tags, spelling errors, and forms of subject headings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…14 While this was a case study of a manual e-book cataloging project rather than a batchloading project, Preston noted that "concerns about bibliographic record accuracy, retrievability, and adherence to cataloging standards" 15 17 She found that the majority of corrections could be viewed as minor and did not affect catalog retrieval, including changes to punctuation, diacritics, and spaces. El-Sherbini also identified corrections that might affect access, including indicators, subfields and delimiters, tags, spelling errors, and forms of subject headings.…”
Section: Literature Reviewmentioning
confidence: 99%